Studies On Parameters of Compost of Kitchen Waste Prepared Using Promising Microbial Consortium - Masurkar, Snehal; Pathade, Girish (Journal of Neonatal Surgery, 2025)
In the present work microbial consortium approach was used to treat the kitchen waste. The kitchen waste contains large amount of organic matter susceptible to microbial degradations. Effective microbial consortium was prepared using bacterial isolates having enzymatic potentials of cellulase, pectinase, amylase, protease, gelatinase and lipase. Microbial consortium, designated as consortium no 7 containing, Micrococcus luteus, Brevundimonas mediterranea, Bacillus tequilensis, Exiguobacterium mexicanum and Serratia marcescens based on maximum enzyme production and thorough compatible with each other. The study on pH, temperature, moisture content, volume, mass & density changes in the kitchen waste was carried out for 30 days using this consortium. It was found out that there was rapid degradation of waste where moisture content, volume and mass were reduced drastically as 10-15%, 35-40%, 10-15%, respectively after 30 days, while there was slight increase in density (0.01-0.03%) pH (0.1-0.2) & temperature ( 40-450C) due to microbial activities. The consortium members were found thermotolerant. The physicochemical parameters of compost (fertilizer) produced in this process indicated that the colour was bit darkened, texture was grainy, no foul smell, the pH near 6.0, % organic matter, K2O, P2O5 & sulfur were 17.8, 0, 45, 0.55 & 0.11, respectively & C: N ratio was increased and all the parameters of fertilizer obtained in the present study are comparable with chemical fertilizer commercially available in the market. The shelf life of the consortium No. -7 was 4-6 months at 40C where CFU/mL was maintained to >108 upto 6 months. In the present studies the compost maturity period was decreased from 25-30 days (without consortium treatment) to 15- 20 days with consortium treatment.